Retention of iron and zinc in yam flour and boiled yam processed from white yam (D. rotundata) varieties - Maziya-Dixon, B.B.; Alamu, Emmanuel Oladeji; Faustina, Dufie W.M.; Asiedu, Robert (Wiley, 2017)
This study investigated the impact of processing on retention of iron and zinc in D. rotundata. Fresh tubers were processed into boiled yam and yam flour and analyzed for zinc, iron, and physicochemical properties. Percent true retention (%TR) was assessed using paired samples and a formula that compensated for loss or gain of moisture and soluble solids. The retention of iron ranged from 55.5% to 98.7% in boiled yam and 25.2% to 54.9% in yam flour; retention of zinc ranged from 49.3% to 97.5% in boiled yam and 18. 9% to 43.1% in yam flour. The amount of iron retained in boiled yam correlated with the amount in the fresh samples (r = .79), likewise in yam flour (r = .82). A similar trend was observed for zinc. From our study, we conclude that retention of iron and zinc is dependent on the variety and processing method used. The information from this study can be used by food scientists and nutritionists in choosing the appropriate processing to increase the retention of high levels of micronutrient in yams and by the yam breeders to adjust their germplasm breeding activities.